A case of squamous cell carcinoma of the lower lip secondary to xeroderma pigmentosum in a child - LI Shiyong, WU Yong, ZHANG Xin, MA Wen, WANG Sihang, FU Shuai (Kouqiang yixue)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder related to XP gene variation, often causing secondary malignant tumors. This article reports a case of a young child with secondary squamous cell carcinoma of the lower lip caused by xeroderma pigmentosum. Through a review of relevant literature, the clinical characteristics, pathogenesis, clinical pathological manifestations, and prognosis of XP are discussed.